A construction of dual box - Ovsienko, S. (Algebra and Discrete Mathematics, 2006)
Let R be a quasi-hereditary algebra, F(∆) and
F(∇) its categories of good and cogood modules correspondingly.
In [6] these categories were characterized as the categories of representations of some boxes A = A∆ and A∇. These last are the box
theory counterparts of Ringel duality ([8]). We present an implicit
construction of the box B such that B − mo is equivalent to F(∇).